257 Participants' Experience of a Novel Group Exercise Program: Results from the DEFRAIL (Diet and Exercise for Frailty) Study Pilot. (16th September 2019) - Bambrick, Pádraig; Phelan, Niamh; Byrne, Thomas; McMahon, Clare; Pope, George; Harrison, Michael; Mulcahy, Ríona; Cooke, John
Abstract: Background: DEFRAIL (Diet and Exercise for Frailty) is a translational study examining the effect of an eight-week multicomponent group exercise program and protein supplementation on frailty in older adults. As part of the development of this novel intervention, a four-week pilot was carried out to assess participants' experience of the program, with a view to optimising the final format. Methods: Inclusion in the DEFRAIL study requires a candidate to be deemed frail as per the Fried criteria. During the initial stages of recruitment for DEFRAIL, any individual who was identified as pre-frail was offered the opportunity to participate in the pilot trial (11 x 1-hour group sessions at a local sporting facility). Following its conclusion, a telephone interview using a standardised questionnaire was conducted on all participants to assess various aspects of their experience. Results: Of 9 participants recruited for the pilot, 7 completed the four-week program (One participant failed to attend any sessions due to difficulties with transport and one participant withdrew after the first week, reporting excessive fatigue as the main issue). Amongst these 7 individuals, attendance was 90.9%. The only other adverse events recorded were delayed-onset muscle soreness (DOMS) in 4 out of 7 and aggravation of a pre-existing joint injury in one individual (neither of which prevented participation in subsequent classes). All attendees reporting enjoying the program with additional feedback obtained via the questionnaire regarding the timing, duration, frequency and intensity of classes, in addition to identifying potential barriers or enablers to participation. Conclusion: This pilot of a novel exercise program for older adults was enjoyed and well-tolerated by pre-frail older adults. Participant feedback, both during the pilot and through a standardised questionnaire following completion, has had a meaningful impact on the final version of the exercise program that will be used for frail older adults in the DEFRAIL intervention.